Pengaruh Peer Education Terhadap Pengetahuan dan Sikap Remaja Putri Tentang Asuhan Prakonsepsi di Pondok Pesantren Darul Fatwa Kwanyar - Sri Rahmawati; Riska Dwi Pramita Sari (Universitas Malahayati Lampung, 2023)
ABSTRACT Health promotion, pregnancy prevention, and reproductive planning are important and fundamental elements of preconception care that can reduce the risk of pregnancy. Adolescence is the right time to provide helpful information to improve health. Many methods can be used to increase knowledge and attitudes among teenagers regarding preconception care, including peer education and leaflets. This study aims to determine the effect of peer education on the knowledge and attitudes of adolescent girls regarding preconception care. Quasi-Experimental research type with a